Exposure-relevant microplastic characteristics in drinking water and estuarine environments: environmental parameters for musculoskeletal experimental research - Muhammad Adil Malik; Song Wu; Wenxiu Zhang; Junjie Huang; Xu Cao; Muhammad Salman Azhar (Frontiers in Public Health, 2026)
Background Microplastics are heterogeneous environmental contaminants whose transport, persistence, and potential biological interactions may depend on particle morphology, size, geometry, and polymer composition. Environmental monitoring studies commonly describe particle occurrence within individual matrices, whereas experimental studies frequently use standardized particles that may not adequately represent environmentally observed configurations. Objective This study aimed to characterize microplastic morphology, dimensional characteristics, size distribution, and polymer composition in drinking-water and estuarine datasets and to identify environmentally observed particle profiles that may inform future musculoskeletal research. Methods Two publicly available environmental datasets were analyzed separately. Overall morphology was summarized across 44,221 San Francisco Bay particle records with valid classifications. For matrix-level analyses, quality-assurance samples were excluded, and sample-level morphology proportions were compared using permutational multivariate analysis of variance based on Bray–Curtis dissimilarities with 9,999 permutations. Homogeneity of multivariate dispersion was assessed using PERMDISP. Particle length and aspect ratio were analyzed using generalized estimating equations accounting for particles clustered within samples and adjusted for environmental matrix. Drinking-water records were analyzed descriptively because of heterogeneity in observational units and analytical methods. Results In the complete archived particle inventory, fibers were the most frequently recorded morphology (49.8%, n = 22,012), followed by fragments (40.3%, n = 17,804). Among 266 environmental or biological samples retained for inferential analysis after exclusion of quality-assurance samples, sample-level morphology profiles differed significantly among matrices (PERMANOVA pseudo- F = 34.14, R2 = 0.344, p < 0.001), although multivariate dispersion also differed (PERMDISP F = 94.31, p < 0.001). In cluster-adjusted models, fibers were approximately 2.51 times longer than fragments (95% CI, 2.35–2.68) and had 24.76 times their aspect ratio (95% CI, 22.70–27.01). Conclusion Environmental microplastics occurred as heterogeneous combinations of fibers, fragments, particle sizes, and polymer categories. These environmentally observed combinations of morphology, dimensions, and material identity may provide empirically grounded parameters for selecting more representative particles in future cartilage-, synovium-, and bone-related experimental studies. However, this study does not measure human intake, internal exposure, tissue accumulation, biological responses, or musculoskeletal outcomes and therefore does not establish toxicological risk, clinical association, or causality.